Numbers and population trends of Cory’s Shearwater Calonectris diomedea at Selvagem Grande, Northeast Atlantic - Granadeiro, José Pedro (2012)
The island of Selvagem Grande holds one of the most important colonies Cory’s Shearwater (Calonectris diomedea) in the Atlantic. Historical records suggest a stable population well in excess of 100,000 pairs. A succession of massacres in 1975 and 1976 dramatically reduced this population to less than 10% of the original numbers. Since 1977 strict protection was enforced and the population started a steady recovery. However, between 1995 and 1998 an alarming decline, of more than 13% of the birds, was reported and concurrently the monitoring work was interrupted. Data from other colonies in the Atlantic and the Mediterranean also indicated significant regional declines, some of which appear to be driven by unsustainable levels of accidental mortality in fishing gear. In order to investigate the persistence of the regressive trend at Selvagem Grande, we carried out a global census of the colony in June 2005. We counted 20,555 occupied nests and estimated the total breeding population at 29,540 pairs. The population still appears to be recovering from the massacres of 1975-1976, at an average rate of about 4.6% per year over the past 25 years. Our data reveal that Selvagem Grande now harbors the largest known Cory’s Shearwater colony in the World. Results from this study suggest that this population is not, as yet, suffering from unsustainable fisheries-related mortality, which would be reflected in a decline in numbers. This situation contrasts with that of the Mediterranean, where significant mortality in fishing gear has been linked to shearwater population declines.